Культурне різноманіття як ресурс для розвитку мовленнєвих навичок особистості - Чопак Єва; Csopák Éva; Chopak Yeva (Видавництво «Код», 2025)
Резюме. У статті розглядаються особливості полікультурного виховання дітей молодшого шкільного віку в умовах сучасного освітнього середовища. Автор акцентує увагу на важливості формування в учнів полікультурної компетентності як основи для толерантної взаємодії у багатокультурному суспільстві. Проаналізовано психологічні та педагогічні аспекти розвитку дітей 6–10 років, зокрема еволюцію когнітивних процесів, естетичних переживань та готовності до міжкультурного спілкування.

Abstract. This article examines the peculiarities of multicultural education for children in primary school age within the context of the modern educational environment. The author emphasizes the importance of developing multicultural competence in students as the foundation for tolerant interaction in a multicultural society. Psychological and pedagogical aspects of the development of children aged 6-10 years are analyzed, including the evolution of cognitive processes, aesthetic experiences, and readiness for intercultural communication. The main tasks of multicultural education are defined, which involve enriching knowledge about the culture of one’s own nation, fostering interest in world cultures, and promoting tolerance in relationships with others. Pedagogical conditions for the effective implementation of multicultural education in the educational process are outlined, including the integration of elements of various cultures into the curriculum, cooperation with the community, and creating an atmosphere of mutual respect in the school environment. In particular, the pedagogical conditions of interaction in a multicultural environment are highlighted: humanization of relations between members of the school team, which is based on the pedagogy of partnership and interaction on the principle of «subject-subject»; pedagogy of the socio-cultural space of the school through increased cooperation with parents, graduates and community representatives; continuity of education and upbringing, which ensures the gradual and holistic formation of the student’s personality. Particular attention is paid to the methods of multicultural education that contribute to the development of multicultural competencies in all participants of the educational process — students, teachers, parents, and members of the local community. The conclusion is made that multicultural education is a key factor in preparing children in primary school age for life in a globalized world.
Cultural diversity as a resource for the development of personal speech skills
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00015728 Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-11
Keywords: полікультурне виховання; молодший шкільний вік; толерантність; міжкультурне спілкування; педагогічні умови